2010
DOI: 10.2147/cpaa.s8657
|View full text |Cite
|
Sign up to set email alerts
|

A common variant in the adiponectin gene on weight loss and body composition under sibutramine therapy in obesity

Abstract: In this study, we aimed to explore whether a common single nucleotide polymorphism (SNP), rs266729 (−11,377C > G), in the adiponectin C1Q and collagen domain containing (ADIPOQ) gene could influence weight reduction and fat change under sibutramine therapy in an obese population. There were 131 obese Taiwanese patients, including 44 in the placebo group and 87 in the sibutramine (10 mg daily) group. We assessed the measures of weight loss and body fat reduction at the end of the 12-week treatment period by ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…A remarkable upregulation of adiponectin levels was observed in NAFLD patients, which is consistent with the conclusion of a recent systemic review. 20 In line with the previous studies, 34 , 39 this study found a positive correlation of increased adiponectin level with weight loss in orlistat group supporting the assumption that adiponectin may be under a feedback regulation by reduction in body weight. 40 It was also noted that there was a positive correlation between increased adiponectin levels and the degree of reduction in NAFLD US grades in orlistat group, similar to the findings of Harrison et al 33 This study also supports the agreement of the previous study that upregulation of adiponectin levels might be a therapeutic approach for the management of NAFLD.…”
Section: Discussionsupporting
confidence: 90%
“…A remarkable upregulation of adiponectin levels was observed in NAFLD patients, which is consistent with the conclusion of a recent systemic review. 20 In line with the previous studies, 34 , 39 this study found a positive correlation of increased adiponectin level with weight loss in orlistat group supporting the assumption that adiponectin may be under a feedback regulation by reduction in body weight. 40 It was also noted that there was a positive correlation between increased adiponectin levels and the degree of reduction in NAFLD US grades in orlistat group, similar to the findings of Harrison et al 33 This study also supports the agreement of the previous study that upregulation of adiponectin levels might be a therapeutic approach for the management of NAFLD.…”
Section: Discussionsupporting
confidence: 90%
“…Aside from rs822396, the other significant genetic findings at 12- or 18-month time points were interactions among rs266729 ( ADIPOQ ), rs1342387 ( ADIPOR1 ), and rs7539542 ( ADIPOR1 ). In addition to also having associations with risk of prostate and colon cancer, type 2 diabetes, and ischaemic stroke, these SNPs have been linked to coronary artery disease, hypertension, and efficacy of weight loss products such as sibutramine (Hegener et al , 2006; Siitonen et al , 2006; Kaklamani et al , 2008b; Hsiao et al , 2010; Han et al , 2011; He et al , 2011; Liu et al , 2011; Kaklamani et al , 2011b; Mather et al , 2012; Mtiraoui et al , 2012; Yang et al , 2012; Zhang et al , 2012). Receiver operating characteristic analysis of an epistatic model of significant SNPs on multivariate analysis only showed AUC of 0.24 for 18-month weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Although sibutramine has been withdrawn from the market, pharmacogenomic studies have identified several gene variants associated with weight loss response. In a Taiwanese population, variants in the adiponectin and uncoupling protein 2 genes have been associated with body fat loss [62,63]. Four studies have shown an association between weight loss response to sibutramine and the C825T variant of the GNB3 gene (which is associated with increased activation of the G-protein β3 subunit [64][65][66][67]).…”
Section: Pharmacogenomicsmentioning
confidence: 99%